Combining Exergame Training with Omega-3 Fatty Acid Supplementation: Protocol for a Randomized Controlled Study Assessing the Effect on Neuronal Structure/Function in the Elderly Brain - Schättin, Alexandra; de Bruin, Eling D. (Frontiers in Aging Neuroscience, 2016)
A common problem in the older population is the risk of falling that might lead to injury, immobility, and reduced survival. Age-related neuronal changes, e.g. decline in grey- and white-matter, affect neuronal, cognitive, and motor functioning. The improvement of these factors might decrease fall events in elderly. Studies showed that the sole administration of video game-based physical exercise, a so-called exergame, or omega-3 fatty acid (FA) may improve motor and/or cognitive functioning through neuronal changes in the brain of older adults. The aim of this study is to assess the effects of a combination of exergame training with omega-3 FA supplementation on the elderly brain. We hypothesize that an intervention using a combination approach differently effects on the neuronal structure and function of the elderly’s brain as compared to the sole administration of exergame training. The study is a parallel, double-blinded, randomized controlled trial lasting 26 weeks. Sixty autonomous living, non-smoking, and right-handed healthy older (>65 years) adults who live independently or in a senior residency are included, randomized, and allocated to one of two study groups. The experimental group receives a daily amount of 13.5ml fish oil (including 2.9g of omega-3 FA), whereas the control group receives a daily amount of 13.5ml olive oil for 26 weeks. After 16 weeks, both groups start with an exergame training program three times per week. Measurements are performed on three time-points by treatment blinded investigators: pre-intervention measurement, blood sample after 16 week, and post-intervention measurements. The main outcomes are motor evoked potentials of the right M. tibialis anterior (transcranial magnetic stimulation) and response-related potentials (electroencephalography) during a cognitive test. For secondary outcomes, reaction times during cognitive tests and spatio-temporal parameters during gait performance are measured. Statistics will include effects sizes and a 2x2-ANOVA with normally distributed data or the non-parametric equivalent for data not fulfilling normal distribution. The randomized controlled study is the first to investigate the effectiveness of exergame training combined with omega-3 FA in counteracting age- and behavioural-dependent neuronal changes in the brain. We hypothesize that an intervention using a combination approach differently effects on the neuronal structure and function